Psychometric Properties of the Premarital Sexual Permissiveness Scale of Reiss (PSP) - Alberto Alarcón-Diaz, Mitchel (2022)
Sexuality is a very important issue in the life of a person and society. Issues such as premarital sexual permissiveness are necessary to understand because it is related to having a flexible attitude towards sexual practices regardless of the emotional bond. Therefore, this research seeks to explore the psychometric properties of the scale of premarital sexual permissiveness of Reiss (PSP) in a group of high school students. In this sense the study offers evidence of validity and reliability of the PSP translated for a Peruvian sample. Regarding the methodology, the research is of psychometric and technological type; the scale of premarital sexual permissiveness of Reiss (PSP) was used with the participation of 1013 female students of national schools of Lima of the last years of the regular basic education; a non-probabilistic type sampling was used - by judgment. Evidence of content validity was found through the criteria of judges, through the V. of Aiken with acceptable values p>0.80; construct validity was evaluated with the Confirmatory Factor Analysis obtaining an X2/gl=2.697, GFI=0.985, CFI=0.982, AGFI=0.973, SRMR=0. 0312 and the reliability was found by Cronbach's Alpha coefficient=0.801 and Omega=0.804; these results indicate that the PSP scale can be used efficiently in a Peruvian sample to evaluate autonomy and acceptability on premarital sexual permissiveness because it has all the required psychometric properties